PELAKSANAAN KEBIJAKAN UJIAN AKHIR SEKOLAH PADA MASA PANDEMI COVID 19 DI SMA SWASTA NAMIRA (UJIAN ONLINE BERBASIS ANDROID) - Budi Budi (Hijri, 2021)
This study was conducted to reveal final school examination policy during the covid-19 pandemic, the research method used was qualitative. the results of the research in the form of implementing the end of semester/school exams are not effective and efficient to be done online, because there are several obstacles, especially in terms of monitoring students during the exam, even though this is the only way the government must take for the learning process to take place during this covid 19 pandemic. The obstacles faced in the implementation of school/semester final exams during the Covid-19 pandemic were that the author had also discussed them in the discussion chapter, namely there were several obstacles, namely the lack of effective monitoring (limitations of remote technology), student saturation in following the process. In online learning, attitude assessment, which is prioritized in terms of ranking (ranking), has also experienced a decline in attitude/morals.School, Policy, During